Celso Almuiña Fernández, Ricardo Martín de la Guarcia, José-Vidal Pelaz López (2016): Perfiles de periodistas contemporáneos - López Romero, Laura (RIHC. Revista Internacional de Historia de la Comunicación, 2016)
Perfiles de periodistas contemporáneos Celso Almuiña Fernández Ricardo Martín de la Guardia José-Vidal Pelaz López (directores) Fragua, Madrid, 2016 424 pp.